الرؤية الاستراتيجية الدولية للشرق الأوسط: الموقع – الثروة-القوة - الجنابي حازم حمد, موسى (جامعة الوادي University of Eloued, 2019)
الملخص ركز البحث على الرؤية الاستراتيجية الدولية للشرق الأوسط، إذ انطلقت تلك الرؤى من مثلث الهيمنة الاستراتيجي (الموقع الاستراتيجي -الثروة النفطية -القوة التحالفية)، فللشرق الأوسط دور في ميزان القوة الاستراتيجي، وتضمنت العملية البحثية مفهوم الرؤية الاستراتيجية الدولية التي تحدد السلوك القوى في شرق الأوسط ضمن أحد الخيارات الثلاث :الأول: الهيمنة على الموقع الاستراتيجي العالمي، والثاني: الهيمنة على مصدر الطاقة العالمي، والثالث: بناء التحالفات والتآلفات الدولية، وتتأثر تلك الخيارات بالقوة، والقرب الجغرافي، وأجمالي القدرات والإمكانات، والنوايا التي يملكها الفاعلين الدوليين، ولعدم تساوي كفتي ميزان القوى الدولية؛ اختل ميزان القوى في الشرق الأوسط وشاع التهديد الإقليمي التحالفي؛ لتكون النوايا الدولية العدوانية اكثر شيوعاً من النوايا الدولية السلمية في التعاطي مع قضايا الشرق الأوسط، إذ أدخلت الشرق الأوسط بدوامة من المشاكل والرهانات، ولتجنب الانهيار أو الانتحار السياسي لابد من بناء رؤية استراتيجية لهندسة العلاقات الشرق أوسطية. :Abstract The research focused on the international strategic vision of the Middle East, starting from the triangle of strategic hegemony (strategic location - oil wealth - the coalition power). The Middle East has a role in the strategic balance of power. The research process included the concept of international strategic vision that defines the strong behavior in the Middle East In one of the three options: the first is to dominate the global strategic position, the second is to dominate the global energy source, and the third is to build alliances and international coalitions. These options are influenced by force, geographical proximity, total capabilities and potentials, J owned by international actors, and not equal to a boy the international balance of power; tipped the balance of power in the Middle East and popularized regional threat to allied; to be the international intentions of aggression more common than international intentions of peace in dealing with Middle East issues, as it introduced the Middle East spiral of problems and bets, and to avoid Political Collapse or Suicide A strategic vision for the engineering of Middle Eastern relations must be built.
international Strategic Vision For The Middle East ((location -wealth -power))
Keywords: الرؤية الاستراتيجية الدولية، الشرق الأوسط، مثلث الهيمنة الاستراتيجي، الموقع، الثروة، القوة، المستقبل; International Strategic Vision, Middle East, such as strategic hegemony, Location, Wealth, Power, Future